FAKTOR DETERMINAN YANG MEMPENGARUHI PEMBERIAN ASI EKSKLUSIF PADA IBU POSTPARTUM DI PUSKESMAS GATAK SUKOHARJO - Mustikaningrum, Fitriana; Salsabila, Almeyda; Kisnawaty, Sudrajah Warajati; Firmansyah, Firmansyah (Jurnal Gizi dan Pangan Soedirman, 2023)
Some of factor that affect the exclusively breastfeeding are mother age, working status, mother’s education and postpartum anxiety. Postpartum anxiety could hamper the releasing of breast milk from mothers. The exclusively breastfeeding in Gatak Primary Health Center in Sukaharjo was still below the national target (38,1%). The aim of study was to analysed the determinant factor that could affect exclusive breastfeeding, including mother age, working status, education and postpartum anxiety of postpartum mother in the Gatak Primary Health Center, District of Sukoharjo, Central Java. This study was observational study with a cross-sectional approach. The sample size of this study was 70 mothers. The sample was taken using simple random sampling. Data on postpartum anxiety was obtained through interviews and the completion of the Postpartum Specific Anxiety Scale Research Short Form (PSAS-RSF) questionnaire. The data of the exclusive breastfeeding, mother’s age, occupation and education were obtained from interviews and questionnaire. The results showed there was no relationship between postpartum anxiety and breastfeeding patterns in the Gatak Primary Health Center, District of Sukoharjo, with p-value of 0.12 (p-value> 0.05), but there was relationship between mother’s age, and working status with exclusive breastfeeding with p value <0,05 in Gatak Primary Health Care Sukoharjo.